Direito territorial e remanescentes das comunidades de quilombo: os entraves à aplicação do art. 68 do ato das disposições constitucionais transitórias de 1988 pelo estado do Pará - ALVES, Luana Nunes Bandeira (Universidade Federal do Pará, 2018)
The present research aimed to verify the execution of quilombola territorial politic starting the based in the diagnosis of the obstacles related to the application of art. 68 of the Transitional Constitutional Provisions of 1988. The analysis clipping is limited in the Pará state territory. The area object of this study denotes specific problems related to the recognition of the territories traditionally occupied by the remnants of quilombo communities. In this sense, for to get results observed in the final of this research were realized a bibliographic survey, a data collect and an analysis of the processes in the land agencies responsible for the execution of the public politics of the quilombola land. The results of the research are presented during the three sections of this dissertation. In the first section is exposed the historic of territorial right of the remnants of quilombo communities in the country since the Brazil colonia until nowadays, highlighting the different forms of actuation of Public Power related to said groups. In the second moment are presented the different legal possibilities to access land by the quilombola groups, highlighting the recognition of the territories situated in Pará state. In the last section were highlighting the principals obstacles diagnosed during the research related the conclusion of the titration processes in the federal sphere of Pará. In the final, it was concluded that, in spite of existence of the law that formally envisaged the necessary titration of quilombola territories, in the scope of execution of this territorial politic were verified obstacles related to the emission of certification by the Palmares Cultural Foundation and elaboration of the Delimitation and Identification of Technical Report; to configuration of conflicts between the own communities or between this groups and the external agents; and to the questions referring to the actuation sphere of land agencies in the state and federal areas.